Candidatus Actinochlamydia pangasiae sp. nov. (Chlamydiales, Actinochlamydiaceae), a bacterium associated with epitheliocystis in Pangasianodon hypophthalmus. Issue 2 (22nd September 2017) - Sood, N; Pradhan, P K; Verma, D K; Yadav, M K; Ravindra,; Dev, A K; Swaminathan, T R; Sood, N K
Abstract: Chlamydial infections are recognised as causative agent of epitheliocystis, reported from over 90 fish species. In the present study, the farmed striped catfish Pangasianodon hypophthalmus (14–15 cm, 70–90 g) with a history of cumulative mortality of about 23% during June and July 2015, were brought to the laboratory. The histopathological examination of gills from the affected fish revealed presence of granular basophilic intracellular inclusions, mostly at the base of the interlamellar region and in gill filaments. A concurrent infection with Trichodina spp., Ichthyobodo spp. and Dactylogyrus spp. was observed in the gills. The presence of chlamydial DNA in the gills of affected fish was confirmed by amplification and sequencing of 16S rRNA gene. BLAST‐n analysis of these amplicons revealed maximum similarity (96%) with Candidatus Actinochlamydia clariae. On the basis of phylogenetic analysis, it was inferred that the epitheliocystis agents from striped catfish were novel and belonged to the taxon Ca . Actinochlamydia. It is proposed that epitheliocystis agents from striped catfish will be named as Ca . Actinochlamydia pangasiae. The 16S rRNA gene amplicons from novel chlamydiae were labelled and linked to inclusions by in situ hybridisation. This is the first report of epitheliocystis from India in a new fish host P. hypophthalmus .